Miskonsepsi Mahasiswa Menggunakan Four-Tier Diagnostic Test - Ratna Dwi Rahayu (SIMETRIS, 2021)
In physics learning, it is not uncommon to find misconceptions experienced by students, including the Dynamic Fluids sub-material, namely the Principle of Continuity. This study aims to identify misconceptions that occur in the Continuity Principle teaching material and identify concept weaknesses as the cause of the Continuity Principles teaching material and identify conceptual weaknesses as the cause of these misconceptions. The study was conducted on 37 students at Seolah Tinggi Tenologi Ronggolawe majoring in Mechanical Engineering with one shoot research method. Diagnosis of student misconceptions is carried out using a four-tier diagnostic test instrument which is the development of a three-tier test instrument by adding the level of confidence in the answers to the third tier. The results of the diagnosis show that students experience misconceptions in the Continuity Principles sub-material by 28%, students who understand partly 35%, students who understand concepts only 6%, students who do not understand concepts by 30% and students who cannot be coded 0%. Based on the results of observations in learning and analysis of the answers to the third and fourth tiers, the misconceptions that occur are generally caused by students' inaccurate logic, namely students assume that a fluid with a high velocity has a large fluid pressure, and vice versa.